Efektivitas Program Pendidikan Agama Di Sekolah Dasar Islam Terpadu Al-Munaya Terhadap Pembentukan Karakter Siswa - Savera, Sari; Mariah, Siti (EL-EMIR Institute, 2025)
This study aims to examine the effectiveness of the Islamic Religious Education (PAI) program in shaping students' character at Al-Munaya Integrated Islamic Elementary School. The research uses a qualitative method with a combination of literature review and field research approaches. Data collection techniques include observation, interviews, and documentation, involving the school principal, subject teachers, and students’ parents. The findings indicate that the implementation of the PAI program consists of three main stages: planning, implementation, and evaluation. Supporting factors in character development include strong school commitment, active parental involvement, and a supportive environment that encourages religious activities such as Quran study groups. On the other hand, inhibiting factors include a lack of parental supervision, PAI activities that are not always conducted effectively, and the negative impact of smartphones, such as access to social media, music, videos, and games. Overall, the PAI program is considered fairly effective in developing students' faith, morals, religious values, and humanity.